Development of a prototype for recycling cement packaging: From solid waste to alkali-activated binder - Soares, Ricardo; Fialho, Rosana; Gonçalves, Jardel; Karolina, Sheyla; Souza, Ronny (National Journal of City Management, 2026)
Objective – To develop and present a prototype for the processing of contaminated cement bags through alkaline treatment with NaOH solution, aiming at their reuse as a construction material.Methodology – An experimental approach was adopted, involving the assembly and monitoring of the prototype and the alkaline treatment of the waste, the recovery of a solid fraction, and the reuse of the residual NaOH solution in the production of an alkali-activated binder combined with silica fume and metakaolin.Originality/Relevance – Contaminated cement bags represent an abundant solid waste in cities, with limited reuse alternatives. This study addresses this gap by proposing an integrated strategy for the valorisation of both solid and liquid fractions.Results – The prototype processed approximately 30 cement bags using 4 L of NaOH solution. The recovered solid material exhibited fine particle size and potential for application in construction materials. The residual NaOH solution was reused in the production of an alkali-activated binder, forming a system similar to N-A-S-H gel, with a molar ratio (SiO₂/NaOH) of 6.41. The material showed an initial setting time of 51 minutes, a final setting time of 10 hours, and compressive strength of up to 1.46 MPa at 60 days.Theoretical/Methodological Contributions – The study demonstrates the technical feasibility of integrated reuse of solid and liquid waste streams through alkaline processing.Social and Environmental Contributions – The results indicate potential for reducing the disposal of cement bags and the consumption of Portland cement, as well as contributing to circular economy strategies in the construction sector by promoting more sustainable waste management practices.
Keywords: Binder; Circular economy; Cement bags